Philosophy and politics in the thought of John Wyclif - Lahey, Stephen E. (Cambridge, U.K. ; New York : Cambridge University Press, 2003)
John Wyclif was the fourteenth-century English thinker responsible for the first English Bible, and for the Lollard movement. In contrast with most other commentaries, this book argues that Wyclif's political programme was based on a coherent philosophical vision ultimately consistent with his earlier reformative ideas.
Cover; Half-title; Series-title; Title; Copyright; CONTENTS; ACKNOWLEDGEMENTS; ABBREVIATIONS; Chapter 1 THE HISTORIOGRAPHY OF WYCLIF'S DOMINIUM THOUGHT; Chapter 2 WHY DOMINIUM?; Chapter 3 WYCLIF'S REALISM AND DIVINE DOMINIUM; Chapter 4 PROPRIETAS IN WYCLIF'S THEORY OF HUMAN DOMINIUM; Chapter 5 IURISDICTIO IN CIVIL DOMINIUM; Chapter 6 ON KINGSHIP; CONCLUSION; BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 225-232) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Wycliffe, John, -- -1384 -- Contributions in doctrine of church and state; Wycliffe, John, -- -1384.; Wycliffe, John, -- -1384; Wyclif, John; Church and state -- England -- History -- To 1500.; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Church and state; England; Politische Philosophie; Politieke filosofie; To 1500; History